A linked administrative data study examining the association between patterns of self-reported functional impairment and mortality in the ageing (65+) population in Northern Ireland. - de Cock, Paul; Ferry, Finola; Rosato, Michael; Curran, Emma; Leavey, Gerard (International Journal of Population Data Science, 2018)
Background The 2011 Northern Ireland Census asked whether individuals considered themselves to have a ‘limiting long-term health problem or disability’. This question was followed by 11 questions as to the nature of the long-term (12+ months) functional impairment(s) people are experiencing (problems with: hearing, sight, communication, mobility, learning difficulties, mental health, pain, breathing, memory, chronic conditions or other conditions). Objectives The purpose of this study was to assess in what way selfreported functional impairment and disability predicts all-cause mortality in older people (age 65+) while taking into account socio-economic and demographic variables. Method The sample includes all individuals in Northern Ireland above age 65 at the time of the Census (2011). Data from the Census was linked to mortality data from Northern Ireland for 33 months after the time of the Census. To assess patterns of selfreported functional impairment, latent class analysis was used to derive groups of individuals who reported similar patterns on the 11-item list of functional impairments. These patterns were used to predict subsequent mortality, while controlling for demographic and socio-economic background factors. Findings Preliminary results indicate the presence of four classes of self-reported functional impairment which can be described as: 1) Low impairment, 2) Pain/Mobility problems, 3) Cognitive/ Mental impairments, 4) Sensory and mobility problems. Initial analyses indicate that these classes were associated with large differences in subsequent mortality. Conclusions Disability and functional impairment questionnaires can be effective tools to describe observed differences in mortality.